Shake-table tests of a 3-story masonry-infilled RC frame retrofitted with composite materials - Koutromanos, Ioannis A.; Kyriakides, Marios; Stavridis, Andreas N.; Billington, Sarah L.; Shing, P. Benson (My University, 2013)
Abstract This paper presents a study that investigated the effectiveness of retrofitting unreinforced masonry infill walls with composite materials to enhance the seismic performance of infilled nonductile RC frames. The primary retrofit scheme considered was the use of engineered cementitious composite overlays. Shake-table tests were conducted on a 2/3-scale, 3-story, 2-bay, masonry infilled RC frame that had one bottom-story wall retrofitted with engineered cementitious composites. The influence of this retrofit on the performance of the structure was investigated using the experimental observations and results of nonlinear finite element analyses. Furthermore, after walls in the second story of the structure were damaged, they were repaired by injecting epoxy into cracked mortar joints, and strengthened with a glass-fiber reinforced polymer overlay. It has been shown that both retrofit schemes are effective in enhancing the seismic performance of the structure and preventing diagonal shear failures of the RC columns.
Keywords: Composite materials; Engineered cementitious composite; Fiber-reinforced polymers; Masonry infill; Nonductile frame; RC; Retrofit techniques; Seismic performance; Shake table